Science networking: role of online encyclopaedias - Jermen, Natasa; Jecic, Zdenko (Circumscribere International Journal for the History of Science, 2018)
This paper discusses the role of online encyclopaedias as a specific component of the scientific infrastructure, using the example of the Croatian encyclopaedistics. The functionalities of digital media generated new epistemic characteristics of encyclopaedias by transforming them into the active platforms for dissemination and generation of new knowledge. Thanks to their role in synthesis, networking and generation of knowledge, online encyclopaedias might be applied to history of science and technology research, in which multi-layered, interdisciplinary approach is obligatory. The recently initiated open-access Croatian Encyclopaedia of Technology and its role in elaborating the field’s knowledge are described. This encyclopaedia is the framework for the development of the Portal of Croatian Technology Heritage, which will serve as a platform for networking and sharing information from various sources. The portal will contribute to the development of research in history of technology, but also to the revalorisation and the sustainability of the national technology heritage and the positioning of Croatian technology in the global context.